THE INFLUENCE OF MEDICAL TEAM INTERPERSONAL COMMUNICATION ON PATIENT SATISFACTION (SURVEY OF COVID 19 PATIENTS IN DKI JAKARTA) - Nuryani Nuryani; Siti Hamidah; Mustofa Mustofa (Dinasti Publisher, 2021)
The Covid 19 pandemic is still growing, people must remind each other to comply with health protocols and government appeals so that there will not be a surge. Patients who are contaminated with Covid-19 usually require a medical team to communicate about the effects they are feeling. Interpersonal communication that exists between the medical team and the patient must be effective. This case is to determine the effect of interpersonal communication between the medical team and patients on the level of patient satisfaction. The correlation results obtained are 0.704, which means that there is a strong relationship between interpersonal communication on patient satisfaction and the results of hypothesis testing indicate that there is an influence between interpersonal communication of the medical team and patients on the satisfaction of patients with Covid 19.